The Influence of the Qiyas Method on the Students' Ability to Understand the Book of Alfiyah Ibnu Malik at Islamic Boarding School - Dede Rizal Munir; Anzar Aquil (Solo Universal Journal of Islamic Education and Multiculturalism, 2023)
This research aims to evaluate the impact of implementing the qiyas method at the Al-Hikamussalafiyah Islamic boarding school on students' understanding of the book Alfiyah Ibnu Malik. This research also aims to assess the relationship between the application of the qiyas method and the student's ability to understand the book Alfiyah Ibnu Malik, as well as identify the extent to which the qiyas method influences the students' understanding of the book. This research method involves a survey with a correlational approach and a quasi-experiment with a Nonequivalent Control Group Pre-Test-Post-Test design. The population and sample of this study consisted of all students at the Al-Hikamussalafiyah Cipulus Islamic boarding school. Research data was collected through observation and tests, and analyzed using SPSS version 16.0 software. The results of the research show that at the Al-Hikamussalafiyah Cipulus Islamic boarding school, the qiyas method is applied consistently in every study of the Alfiyah Ibnu Malik book, which is rated in the frequent/good category. The average student test result score is 50.8%. Apart from that, the student's ability to understand the book of Alfiyah Ibnu Malik has an average value of 86.83, with a median of 90.75, and a mode of 98.59, which shows a very good level of understanding.